1988
DOI: 10.1093/ajcn/47.6.976
|View full text |Cite
|
Sign up to set email alerts
|

Effect on blood pressure of two diets differing in total fat but not in saturated and polyunsaturated fatty acids in healthy volunteers

Abstract: The effects of a low-fat, carbohydrate-rich and a high-fat, olive-oil-rich diet on blood pressure were studied under strict dietary control. Forty-seven healthy normotensive men and women were fed a diet high in saturated fatty acids (20 en%) and total fat (38 en%) for 17 d. Twenty-four subjects then received a low-fat, carbohydrate-rich diet (total fat 22 en%) and the other 23 a high-fat, olive-oil-rich diet (oleic acid 24 en%, total fat 41 en%) for 36 d. Both test diets had the same level of saturated fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…Another study in 47 healthy normotensive volunteers showed a reduction of BP after a diet with a high amount of MUFA, from olive oil, compared with a diet rich in SFA. However, in this case, the MUFA diet did not perform better than a high-carbohydrate diet 25 . In women with gestational diabetes, MUFA (from high-oleic sunflower oil) intake prevented the BP increase in the third trimester of pregnancy compared with a diet rich in carbohydrates 34 .…”
Section: Feeding Trialsmentioning
confidence: 62%
“…Another study in 47 healthy normotensive volunteers showed a reduction of BP after a diet with a high amount of MUFA, from olive oil, compared with a diet rich in SFA. However, in this case, the MUFA diet did not perform better than a high-carbohydrate diet 25 . In women with gestational diabetes, MUFA (from high-oleic sunflower oil) intake prevented the BP increase in the third trimester of pregnancy compared with a diet rich in carbohydrates 34 .…”
Section: Feeding Trialsmentioning
confidence: 62%
“…The short duration of the former studies may have been a limiting factor leading to a possible delayed response. Also, in two of the four studies (6,8), the percentage of energy from saturated fat was higher (2-3.2%) and the dietary fiber content was lower (9 -18 g) on the highmonounsaturated fat diet compared with the high-carbohydrate diet. These differences could have mitigated any possible blood pressureϪlowering effect of monounsaturated fat as diets high in saturated fat or low in fiber have been reported to raise blood pressure (13,14).…”
Section: Phases 1 2 and 2 Extension (21 Patients)mentioning
confidence: 94%
“…Lauszus et al (5) reported a greater rise in 24-h ambulatory diastolic blood pressure with a high-carbohydrate diet than with a high-monounsaturated fat diet in women with gestational diabetes. However, Mensink et al (6) found no difference in clinical blood pressure in normotensive subjects randomized to a high-monounsaturated fat or a highcarbohydrate diet. Three cross-over studies, two in type 2 diabetic subjects (7,8) and one in subjects with hyperlipidemia (9), also found no difference in 24-h ambulatory (7) or clinical (8,9) blood pressure on the two diets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the SUN Study, olive oil consumption was also associated with lower risk of developing hypertension but only among men (82) . Also, two interventional studies have demonstrated that a diet rich in MUFA is more capable of reducing blood pressure compared to a diet rich in SFA (83) and, unlike a low-fat, carbohydrate-rich diet, has no deleterious effect on blood pressure in normotensive subjects (84) . A reduction in the use of hypertensive medication was also observed after intake of a diet rich in olive oil, compared to a high PUFA diet (85) .…”
Section: Effect Of the Mediterranean Diet On Hypertensionmentioning
confidence: 99%